Expert Answers
Seema Adiga eNotes educator| Certified Educator

`sum_(n=4)^6 n*6` is nothing but `sum_(n=4)^6 6n`

In this you have to substitute n value  as 4,5,6 (since n= 4 to 6) and add all the values(`sum_` represents addition)     

`therefore`  `sum_(n=4)^6 6n` = `(6*4) + (6*5) + (6*6)`

                                          = `24+30+36`

                                          = `90`

``

``

 

embizze eNotes educator| Certified Educator

Find `sum_(n=4)^6 6n`

This is the sum 6(4)+6(5)+6(6)=90 which is the answer.

An alternative is to "factor" out the 6 and you get 6(4+5+6)=6(15)=90.